Pase del Niño como Patrimonio Cultural Inmaterial en el Imaginario Colectivo de la ciudad de Riobamba, periodo septiembre 2016- febrero 2017. - Cabezas Bastidas, José Martin (2023)
The research work entitled "Child's Pass as intangible cultural heritage in the collective imagination of the city of Riobamba, period September 2016 - February 2017" this project is based on cultural anthropological and structuralist communication theories, which are based on the study of society and its forms of communication and that have as their main axis the relationships of existing social groups. It begins with the problem analysis that is and the definition of the general objective that is to determine the incidence of the Child's Pass as intangible cultural heritage in the collective imagination in the inhabitants of 18 to 60 years of the city of Riobamba, in the period September 2016-February 2017and specific to then continue with the theoretical framework where topics and sub-themes related to the independent variable the Child's Pass as intangible cultural heritage and of the dependent variable the collective imagination are related, continuing with the definition of terms, discussion of results and Operationalization of variables. The research methodology, with a population of 225,741 inhabitants and sample of 384 surveys, techniques and data collection tools and procedural techniques for analysis, for this the survey and interview technique was applied, with these data we proceeded to perform the analysis and interpretation of results to determine their inference with the percentages obtained, the data obtained from the surveys served to determine the conclusions and recommendations. Through the investigation it was concluded that the Passes of the Child are already part of the identity of Riobambeña and that each of its characters is in the collective imagination of the citizens, the Passes of the child opens a great platform for the Tourism and the economy of the city, is why the GADM Riobamba declared in January 2017 as an intangible cultural heritage to the Passes of the child, for being a custom that has been developing for decades, conserving its essence and components that identify it as unique and irreplaceable tradition of the city.